"They come with nothing:" How professional development in a culturally responsive pedagogy shapes teacher attitudes towards Latino/a English language learners. (April 2018) - Mellom, Paula J.; Straubhaar, Rolf; Balderas, Carissa; Ariail, Michael; Portes, Pedro R.
Abstract: Especially in the United States' "New South, " rapid growth in numbers of Latino/a students, particularly Latino/a English Language Learners (ELLs), has resulted in a cultural clash that is reflected in the often prejudiced attitudes of predominantly white monolingual teachers towards such students. Drawing on qualitative data collected as part of a mixed-methods multi-year study of the effects of teacher training in the culturally responsive Instructional Conversation pedagogy on ELL academic outcomes, the authors argue that while New South teacher attitudes towards ELLs often remain prejudiced, Instructional Conversation training seems to mitigate those negative attitudes over time. Highlights: White Southern monolingual teachers often hold prejudiced opinions towards Latino/a students. IC pedagogy helps teachers get to know their Latino/a students in their own words. IC mitigated participating teachers' negative attitudes towards Latino/a students.